Hydrothermal synthesis of hexagonal YMnO3 and YbMnO3 below 250 °C. Issue 28 (2nd July 2021) - Marshall, Kenneth P.; Eidem, Sigurd O.; Småbråten, Didrik R.; Selbach, Sverre M.; Grande, Tor; Einarsrud, Mari-Ann
Abstract : Impact of synthesis parameters on phase purity, microstructure and defect chemistry during the hydrothermal synthesis of h-YMnO3 . Abstract : The hydrothermal synthesis of hexagonal YMnO3 and YbMnO3 are reported using high KOH mineraliser concentrations (>10 M) and low temperatures (<240 °C). The relation between reaction parameters and resulting phase purity were mapped by ex situ and in situ X-ray diffraction. Excess Y2 O3 resulted in two-phase product with hexagonal YMnO3 with different lattice parameters. An unusual microstructure was observed in which particles have a hexagonal shape with a highly crystalline edge and either a hollow or polycrystalline interior. An Ostwald ripening mechanism was proposed to explain this phenomenon. Solid-state reactions and density functional theory calculations were performed to determine plausible defect chemistry which can lead to the observed phases with different lattice parameters.